2017
DOI: 10.1080/14767058.2017.1391784
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antibiotic prophylaxis in cesarean section: retrospective, difference-in-differences estimation of the effect on surgical-site-infection

Abstract: We found no effect of the timing of prophylactic antibiotic administration (prior to surgical incision versus after cord clamping) on SSI rates following CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Mothers delivering by cesarean section (CS) have a five to twenty-fold higher risk of infections than mothers giving birth vaginally and surgical-site infections are more prevalent in CS, than other surgical procedures [ 1 4 ]. Administration of prophylactic antibiotics has the potential to significantly reduce the risk of postoperative infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers delivering by cesarean section (CS) have a five to twenty-fold higher risk of infections than mothers giving birth vaginally and surgical-site infections are more prevalent in CS, than other surgical procedures [ 1 4 ]. Administration of prophylactic antibiotics has the potential to significantly reduce the risk of postoperative infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kết quả nghiên cứu của Jyothirmayi CA và cộng sự [14] cũng chỉ ra rằng nhóm bà mẹ được tiêm kháng sinh trước khi mổ giảm tỉ lệ sốt và nhiễm trùng vết mổ đáng kể so với nhóm dùng sau kẹp rốn. Kết quả này tương tự với nhiều nghiên cứu khác trên thế giới [15], [16]. Trong khi đó, một số nghiên cứu lại cho kết quả tương tự với chúng tôi, rằng không có sự khác biệt về tỉ lệ nhiễm trùng vết mổ liên quan đến thời điểm sử dụng kháng sinh dự phòng trước khi mổ lấy thai hay sau khi kẹp rốn [17][18][19][20].…”
Section: Kết Quả Nghiên Cứuunclassified
“…A recent single site cohort study analyzed this issue, and found no difference in surgical site infections after cesarean sections after a policy change from antibiotic prophylaxis administered after cord clamping to preincision. 33 In addition, Valent et al demonstrated in a randomized controlled trial that 48 hours of cephalexin and metronidazole in addition to the usual practice of preincision cefazolin administration reduced surgical site infections from 15 to 6% in obese women, which was a similar risk reduction from 12 to 6.1% seen in the trial by Tita et al 6,34 If antibiotic prophylaxis after cord clamping in conjunction with postoperative antibiotic regimen were as effective as preincision antibiotic prophylaxis, this would dramatically reduce the exposure of antibiotics to the fetus and reduce their long-term effect.…”
Section: Future Considerations and Solutionsmentioning
confidence: 99%